2017
DOI: 10.18321/ectj583
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Single-Wall Carbon Nanotube Production in the Arc Discharge Process

Abstract: Single-wall carbon nanotubes (SWNTs) promise wide applications in many technical fields. As a result purified SWNT material is sold now on the West market at more than $1000 per 1 gram. Thus developing an effective technology for SWNTs production rises to a very important scientific problem. The perspectives of three existing methods providing raw material in the technology of SWNT production have been analyzed. They are i) pulsed laser evaporation of graphite/metal composites, ii) evaporation of graphite elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(12 citation statements)
references
References 22 publications
0
11
1
Order By: Relevance
“…2), where the spot intensity is indicated on vertical axis. It was found that the images and periodicities observed in a 1D nanocrystal do not correspond to those determined earlier in the works [2,[8][9][10][11][12][13] for 1D CuI@SWCNT nanocomposites. In order to restore the crystalline structure and build an elementary cell of an 1D nanocrystal, we have analyzed a number of images like those shown in Fig.…”
Section: Resultscontrasting
confidence: 65%
See 2 more Smart Citations
“…2), where the spot intensity is indicated on vertical axis. It was found that the images and periodicities observed in a 1D nanocrystal do not correspond to those determined earlier in the works [2,[8][9][10][11][12][13] for 1D CuI@SWCNT nanocomposites. In order to restore the crystalline structure and build an elementary cell of an 1D nanocrystal, we have analyzed a number of images like those shown in Fig.…”
Section: Resultscontrasting
confidence: 65%
“…5. As was mentioned above, no such crystalline structure of the nanocomposite was found in previous studies [2,[8][9][10][11][12][13]. In the process of studying the nanocomposites, CuI nanocrystals were found whose crystalline structure coincides with that determined in other works and their images obtained by STEM in bright field and HAADF modes are shown in Figs.…”
Section: Resultsmentioning
confidence: 48%
See 1 more Smart Citation
“…Synthesis and characterization of the SWCNTs supplied by the company are described in detail. [41][42][43] Synthesis of PIs PI-NH 2 -I and PI-NH 2 -II (Co)PIs PI-NH 2 -I and PI-NH 2 -II were synthesized by onestep high-temperature polycondensation of respective tetracarboxylic acid dianhydrides and diamines in m-cresol at 180 C in accordance with previously reported procedure. 44 Both PI-NH 2 -I and PI-NH 2 -II were prepared at diamines and tetracarboxylic acid dianhydrides molar ratio equal to 1.0:0.9.…”
Section: Methodsmentioning
confidence: 99%
“…The SWCNTs were obtained by the electric arc method using the Ni/Y catalyst and provided by Carbonchg company (http://www.carbonchg.ru). Synthesis and characterization of the SWCNTs supplied by the company are described in detail …”
Section: Methodsmentioning
confidence: 99%